Immunohistochemical Characterization of Canine Oral Papillary Squamous Cell Carcinoma. Issue 2 (March 2018) - Thaiwong, Tuddow; Sledge, Dodd G.; Collins-Webb, Alexandra; Kiupel, Matti
Recently, histologic subtypes of oral squamous cell carcinoma (SCC) corresponding to the human classification scheme have been proposed for dogs. A papillary squamous cell carcinoma subtype is characterized by dominant exophytic architectural growth with limited invasion, a lower metastatic rate, and better overall survival compared with conventional SCC. Whereas most canine oral conventional SCCs are easily diagnosed by histologic examination, the diagnosis of canine oral papillary squamous cell carcinoma (COPSCC) can be challenging since the exophytic portion lacks histologic features of malignancy and appears similar to oral nonviral papillomas. In contrast, the invasive portion of COPSCC has morphologic similarities to conventional SCC and canine acanthomatous ameloblastoma. The goals of this study were to immunophenotype these 3 entities and to potentially identify discriminating markers. A panel of 17 immunohistochemical markers was investigated in tissue microarrays that included 25 COPSCCs, 10 conventional SCCs, and 10 canine acanthomatous ameloblastomas. Additionally, COPSCCs were screened for papillomavirus as a potential cause using immunohistochemistry and in situ hybridization. COPSCC had immunophenotypical similarities with conventional SCC and acanthomatous ameloblastoma, but the combined differences in immunolabeling for AE1/AE3, 34βE12, p63, and calretinin discriminated between the entities. Papillomavirus was not detected in any COPSCC, making a viral pathogenesis unlikely. A better understanding of the immunophenotype of COPSCC will aid in a more accurate diagnosis and potentially improve therapeutic approaches.